Assessing child development scores among minority and Indigenous language versus dominant language speakers: a cross-sectional analysis of national Multiple Indicator Cluster Surveys - Ann C Miller, PhD; David Flood, MD; Scott Tschida, MPhil; Katherine Douglas, MD; Peter Rohloff, MD (Elsevier, 2024)
Summary: Background: Multiple studies have highlighted the inequities minority and Indigenous children face when accessing health care. Health and wellbeing are positively impacted when Indigenous children are educated and receive care in their maternal language. However, less is known about the association between minority or Indigenous language use and child development risks and outcomes. In this study, we provide global estimates of development risks and assess the associations between minority or Indigenous language status and early child development using the ten-item Early Child Development Index (ECDI), a tool widely used for global population assessments in children aged 3-4 years. Methods: We did a secondary analysis of cross-sectional data from 65 UNICEF Multiple Indicator Cluster Surveys (MICS) containing the ECDI from 2009-19 (waves 4-6). We included individual-level data for children aged 2-4 years (23-60 months) from datasets with ECDI modules, for surveys that captured the language of the respondent, interview, or head of household. The Expanded Graded Intergenerational Disruption Scale was used to classify household languages as dominant versus minority or Indigenous at the country level. Our primary outcome was on-track overall development, defined per UNICEF's guidelines as development being on track for at least three of the four ECDI domains (literacy-numeracy, learning, physical, and socioemotional). We performed logistic regression of pooled, weighted ECDI scores, aggregated by language status and adjusting for the covariables of child sex, child nutritional status (stunting), household wealth, maternal education, developmental support by an adult caregiver, and country-level early child education proportion. Regression analyses were done for all children aged 3-4 years with ECDI results, and separately for children with functional disabilities and ECDI results. Findings: 65 MICS datasets were included. 186 393 children aged 3-4 years had ECDI and language data, corresponding to an estimated represented population of 34 714 992 individuals. Estimated prevalence of on-track overall development as measured by ECDI scores was 65·7% (95% CI 64·2-67·2) for children from a minority or Indigenous language-speaking household, and 76·6% (75·7-77·4) for those from a dominant language-speaking household. After adjustment, dominant language status was associated with increased odds of on-track overall development (adjusted OR 1·54, 95% CI 1·40-1·71), which appeared to be largely driven by significantly increased odds of on-track development in the literacy-numeracy and socioemotional domains. For the represented population aged 2-4 years (n=11 465 601), the estimated prevalence of family-reported functional disability was 3·6% (95% CI 3·0-4·4). For the represented population aged 3-4 years with a functional disability (n=292 691), language status was not associated with on-track overall development (adjusted OR 1·02, 95% CI 0·43-2·45). Interpretation: In a global dataset, children speaking a minority or Indigenous language were less likely to have on-track ECDI scores than those speaking a dominant language. Given the strong positive benefits of speaking an Indigenous language on the health and development of Indigenous children, this disparity is likely to reflect the sociolinguistic marginalisation faced by speakers of minority or Indigenous languages as well as differences in the performance of ECDI in these languages. Global efforts should consider performance of measures and monitor developmental data disaggregated by language status to stimulate efforts to address this disparity. Funding: None. Translations: For the Spanish, Kaqchikel and K'iche' translations of the abstract see Supplementary Materials section.